EXPLORING ETHNOMATHEMATICS IN THE ARCHITECTURE OF THE SHEIKH ZAYED MOSQUE IN SURAKARTA AS A REPRESENTATION OF ISLAMIC CULTURE - Mayis Nur Cahyani; Djatmiko Hidajat (Universitas Muhammadiyah Metro, 2025)
This study explores ethnomathematical elements in the architecture of the Sheikh Zayed Grand Mosque in Surakarta as a representation of mathematics in Islamic culture. The method used is qualitative with an ethnographic approach through observation, interviews, and documentation. The results show that the mosque's architecture contains mathematical concepts, such as geometry in the form of cubes, hemispheres, and triangular pyramids, symmetry in wall and floor ornaments, and translation in decorative motifs. These findings indicate that the mosque is not only aesthetically and religiously valuable but also contains mathematical concepts that can be a source of learning. This study concludes that the Sheikh Zayed Grand Mosque can be an interesting medium for ethnomathematics learning, connecting mathematics with Islamic culture, and enriching ethnomathematics studies in Indonesia.